The Polarization of Public Opinion on Weibo about Public Affairs of People’s Livelihood in China - Chen Ziran; Liu Yaohua; Ren Shuyan; Zeng Yutong (SHS Web of Conferences)
Social media has become a key platform for public discussion and dissemination of social events but has also led to the Echo chamber effect and emotional polarization. This study uses the “Jiang Ping incident” as a case to explore emotional polarization in public opinion on Chinese social media platforms, specifically Weibo. The study first reviews relevant theories, including the Echo chamber effect, selective information preference, silence behavior, and opinion-emotional contagion. Then, using a questionnaire survey, empirical data were collected, and factor analysis was conducted to extract key common factors influencing emotional polarization. In the final regression analysis, the impact of these three common factors on the polarization of public opinion groups was further examined. The results show that selective information preference and opinion-emotional contagion have a significant negative impact on emotional polarization. Additionally, silence behavior was also found to have a negative impact on emotional polarization, suggesting that users’ silence behavior in the face of opposing opinions may exacerbate the degree of emotional polarization. Finally, the study provides recommendations for social media platform managers and policymakers to mitigate emotional confrontation on social media and promote more rational public discussion.